Health improvements and health inequality during the last 40 years - Giovanni Andrea Cornia; Leonardo Menchini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper juxtaposes changes over the last forty years in income growth and distribution with the mortality changes recorded at the aggregate level in about 170 countries and at the individual level in 26 countries with at least two demographic and health surveys covering the last twenty years. Over the 1980s and 1990s, the infant mortality rate, under-5 mortality rate, and life expectancy at birth mostly continued the favourable trends that characterized the 1960s and 1970s. Yet, especially in the 1990s, the pace of health improvement was slower than that recorded during the prior decades. In addition, the distribution between countries of aggregate health improvements became markedly more skewed. These trends are in part explained by the negative changes recorded in sub-Saharan Africa and Eastern Europe, but are robust to the removal of the two regions from the sample. This tendency is observed also at the intraregional level, with the exception of Western Europe. Thirdly, demographic and health survey data for 26 developing countries point to a frequent divergence over time in the within-country distribution of gains in the infant mortality and under-5 mortality rates among children living in urban versus rural areas and belonging to families part of different quantiles of the asset distribution. The paper concludes by underscoring the similarities and linkages between changes in income inequality and health inequality and suggests some tentative explanations of these trends without, however, formally testing them.
Keywords: D63; I12; I31; J13; O15; 330; health status; health inequality; income inequality; welfare disparities; Einkommensverteilung; Gesundheit; Welt